Points of view in argumentative discourses dealing with the distribution of the emergency anti-conception drug (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
An argumentative analysis is presented dealing with the dispute about the distribution of an emergency anti-conception drug in the Chilean public health network. The points of view of the Church, the Government and the Chilean scientists are established. To do this, the argument structures are presented, according to the Toulmin model. For us, disputing points of view result from the presence of alternative warrants regarding the same topic. Finally, an analysis of the force and legitimacy of the points of view is developed. The corpus is made ofdiscourses published in the Chilean press after Sunday 2nd of may 2004, day inwhich Cardinal Errarzuriz delivered a message to the faithful attending to the churches in Santiago, being the starting point of the dispute
Keywords: argumentative analysis; Toulmin model; argumentative point of view; emergency anti-conception